Injection molding method and injection molding die
Patent Information
- Application Number
- JP2021127433
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-08-03
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2041-08-03
AI Technical Summary
【0007】 本発明によれば、成形型に細かな凹凸形状を形成することなく細かな凹凸形状を有する成形品を成形することができる。
Smart Images

Figure 0007643245000002 
Figure 0007643245000003 
Figure 0007643245000004
Abstract
Description
[Technical field]
[0001] The present invention relates to an injection molding method and an injection molding mold. [Background technology]
[0002] A molding method is known in which the cavity of a mold is filled with carbon dioxide beforehand and the carbon dioxide is mixed into the injected amorphous olefin resin (Patent Document 1). The addition of carbon dioxide reduces the viscosity and glass transition temperature of the resin, allowing the resin to flow into the fine details of the uneven shape formed on the surface of the mold, making it possible to transfer the fine uneven shape to the molded product. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2001-129853 A Summary of the Invention [Problem to be solved by the invention]
[0004] In the above-mentioned conventional technology, when molding a molded product having a fine uneven shape such as grain (wrinkles), a fine uneven shape corresponding to the desired uneven shape is processed on the surface of a mold, the fluidity of the molten resin is improved by carbon dioxide, and the shape formed on the surface of the mold is then transferred. Therefore, if carbon dioxide cannot be used, the uneven shape on the surface of the mold cannot be transferred to the molded product, and there is a problem that a molded product having a fine uneven shape cannot be molded.
[0005] An object of the present invention is to provide an injection molding method and an injection molding mold capable of molding a molded product having a fine uneven shape without forming a fine uneven shape in the molding mold. [Means for solving the problem]
[0006] The present invention solves the above problem by, when filling a molding material containing a crystalline resin and an additive having a higher elastic modulus and lower shrinkage rate than the crystalline resin into a mold having a plurality of recesses machined into the surface of a cavity, making the recesses into a cone or frustum shape, with the opening side into which the molding material flows as the bottom surface, and the area of the cross section parallel to the bottom surface decreasing as the depth increases, making the maximum length of the bottom surface in the flow direction of the molding material 200 to 400 μm, making the depth of the cone or frustum in a direction perpendicular to the flow direction 40 to 150 μm, and making the ratio of the maximum length of the bottom surface to the depth 1.34:1 to 5:1. Effect of the Invention
[0007] According to the present invention, a molded product having fine irregularities can be molded without forming fine irregularities in the molding die. [Brief description of the drawings]
[0008] [Figure 1] 1 is a vertical cross-sectional view showing an example of an injection molding machine used in the injection molding method of the present invention. [Diagram 2] FIG. 2 is a perspective view showing an example of a plurality of recesses formed on a surface of a cavity. [Diagram 3] 3 is a vertical sectional view of the recess shown in FIG. 2. [Figure 4] 4 is a vertical cross-sectional view showing a molding material filled in the recess shown in FIG. 3. [Figure 5A] 5 is an example of an enlarged image of the molding material M shown in FIG. 4 viewed from above (part 1). [Figure 5B] 5 is an example of an enlarged image of the molding material M shown in FIG. 4 viewed from above (part 2). [Figure 5C] 5 is an example of an enlarged image of the molding material M shown in FIG. 4 viewed from above (part 3). [Figure 6] 4 is an enlarged image of a vertical cross section of the molding material filled in the recess shown in FIG. 3. [Figure 7A] FIG. 11 is a vertical cross-sectional view of another example of a recess. [Figure 7B]7B is a vertical cross-sectional view showing the molding material filled in the recess shown in FIG. 7A. [Figure 8A] FIG. 11 is a vertical cross-sectional view of a recess in yet another example. [Figure 8B] 8B is a vertical cross-sectional view showing a molding material filled in the recess shown in FIG. 8A. [Figure 9A] FIG. 2 is a plan view showing a cavity of an injection molding die used in the examples. [Figure 9B] FIG. 9B shows a nested pattern for the injection mold of FIG. 9A. [Figure 10A] 1 is a table showing the physical properties of polypropylene used in the examples. [Figure 10B] FIG. 2 is a diagram showing the particle size distribution of talc used in the examples. [Figure 10C] FIG. 2 is a diagram showing the melt viscosity of molding materials used in the examples. [Figure 11] 1 is an example of an enlarged image showing the surface state of a molded article molded in an example. [Figure 12] 1 is another example of an enlarged image showing the surface state of a molded article molded in an embodiment. [Figure 13A] 1 is an example of an enlarged image showing the cross-sectional state of a molded product molded in an embodiment (part 1). [Figure 13B] 2 is an example of an enlarged image showing the cross-sectional state of a molded product molded in an embodiment (part 2). [Figure 13C] 1 is another example (part 1) of an enlarged image showing the cross-sectional state of a molded product molded in an embodiment. [Figure 13D] 2 is another example (part 2) of an enlarged image showing the cross-sectional state of a molded product molded in an embodiment. [Figure 14] FIG. 4 is a diagram showing the relationship between the shape of a recess and the glossiness of the surface of a molded article. [Figure 15A] 1 is a table showing the gloss level of each of the produced nesting members. [Figure 15B] FIG. 13 is a diagram showing an oblique image of the produced nest. [Figure 15C] FIG. 16 is an enlarged plan view showing a machined portion of the insert Z of A-01 in FIG. 15. [Figure 15D] FIG. 2 is a graph showing the relationship between the amount of talc added and the glossiness of the surface of a molded article. [Figure 16] FIG. 1 is a diagram showing an example of the water repellency effect of a molded product molded in an example. [Figure 17A] FIG. 2 is an explanatory diagram showing an advancing contact angle and a receding contact angle. [Figure 17B] FIG. 2 is a diagram showing an example of the advancing contact angle of a molded product molded in an example. [Figure 17C] FIG. 2 is a diagram showing an example of the receding contact angle of a molded product molded in an example. [Figure 17D] FIG. 17B shows contact angle hysteresis based on the results of FIGS. 17B and 17C. [Figure 18A] 1 is an enlarged image showing an example of a scratch test of a molded product molded in an example. [Figure 18B] FIG. 1 is a diagram showing an example of scratch resistance of a molded product molded in an example. [Figure 18C] 18B is a further enlarged image of a portion of the enlarged image of FIG. 18A. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, an embodiment of an injection molding method and an injection molding die according to the present invention will be described with reference to the drawings.
[0010] The injection molding method refers to a method of molding metal, plastic, or non-plastic ceramic by injecting a certain amount of molten material, and the injection molding method of the present invention particularly relates to a method of molding a molding material containing a crystalline resin and an additive. Also, the injection molding mold refers to a molding mold into which the material to be molded is supplied from an external heated cylinder, and in the present invention particularly, the material to be molded is a molding material containing a crystalline resin and an additive.
[0011] [Injection molding machine] FIG. 1 is a vertical cross-sectional view showing an example of an injection molding machine used for injection molding. In the injection molding machine 1 shown in FIG. 1, granular molding material M (also called pellets, the same applies below) is charged into a hopper 11, and is supplied from the hopper 11 to a heating cylinder 12. The molding material M supplied to the heating cylinder 12 is heated and melted in the heating cylinder 12. The heating temperature of the heating cylinder 12 is set according to the melting temperature set for each molding material M. The molten molding material M is injected from a nozzle 14 into an injection mold T by moving a screw 13 in the direction of an arrow A. The pressure of the molding material M during injection is, for example, 5 to 100 MPa. The molding material M injected from the nozzle 14 passes through a sprue 15, a runner 16, and gates 17, 17, and is filled into a cavity C of the injection mold T. The temperature of the injection mold T is set according to the mold temperature set for each molding material M. The molding material M filled in the cavity C solidifies while maintaining the shape of the cavity C, so that a molded product having a shape corresponding to the shape of the cavity C is obtained.
[0012] The injection molding die T is a die made of steel such as as-rolled steel, pre-hardened steel, quenched and tempered steel, or aged steel, but copper or a copper alloy (e.g., beryllium copper), which has a higher thermal conductivity than steel, may be used to promote cooling of the molded product. Also, instead of a metal die, a molding die made of resin may be used. Since resin is less conductive to heat than metal, it takes longer for the molding material M to solidify. This promotes crystallization of the molding material M in the skin layer of the molded product, improving the appearance of the molded product.
[0013] As described above, since the molded product has a shape corresponding to the shape of the cavity C, in the past, in order to mold a molded product having a fine uneven shape such as a leather grain pattern, it was necessary to form a fine uneven shape on the surface of the cavity C of the injection molding mold T. Such a fine uneven shape is formed by processing such as etching, sandblasting, laser processing, and ultra-precision machining. However, since the molding material M shrinks when solidifying, it is difficult to accurately transfer the formed fine uneven shape to the surface of the molded product. In particular, when the molding material M contains a crystalline resin, the amount of shrinkage is larger than when an amorphous resin is used, making it difficult to transfer the fine uneven shape. In addition, when the molding material M contains an additive, the effect of the additive on the transfer of the fine uneven shape has not been clarified.
[0014] In the present invention, fine irregularities are formed on the surface of the molded product by utilizing the shrinkage of the resin and the difference in shrinkage between the resin and the additives in the portion of the cavity C that is not in contact with the surface of the injection molding die T. This makes it possible to mold a molded product having fine irregularities such as a leather grain pattern without processing the surface of the cavity C of the injection molding die T to form fine irregularities.
[0015] [Molding material] The molding material M of this embodiment includes a resin and an additive. Since the molding material M is used for injection molding, the resin of this embodiment is a thermoplastic resin that is plasticized by heating. In the present invention, since the shrinkage of the resin is utilized, a crystalline resin is preferable to an amorphous resin. In the crystalline resin, when the molten state changes to the solidified state in the cavity C, a crystalline structure in which a part of the molecular chain is regularly arranged is formed. Therefore, the crystalline resin has a larger volume change rate (i.e., shrinkage rate) than an amorphous resin in which a crystalline structure is not formed and the molecular chains are solidified while being irregularly entangled. Examples of the crystalline resin include polyethylene, polypropylene, polyamide, polyacetal, polyethylene terephthalate, polybutylene terephthalate, polyphenylene sulfide, polyether ether ketone, and polytetrafluoroethylene. Only one type of crystalline resin may be used, or a plurality of types may be used in combination as a polymer alloy.
[0016] Additives are materials that modify resins and improve their performance and function, and include stabilizers, function-imparting agents, and materials that can be combined with resins. Examples of stabilizers include antioxidants, metal deactivators, ultraviolet absorbers, and light stabilizers, while examples of function-imparting agents include plasticizers, flame retardants, nucleating agents, fillers, compatibilizers, curing agents, photoinitiators, clarifiers, antistatic agents, antifogging agents, conductive materials, lubricants, antibacterial agents, and antifungal agents. Examples of materials that can be combined with resins include colorants such as pigments and dyes, reinforcing materials such as glass fibers, carbon fibers, aramid fibers, carbon nanotubes, cellulose nanofibers, talc, and glass beads, and shock absorbing materials such as rubber and elastomers. These additives are mixed uniformly with resins using melt kneaders such as single-screw and twin-screw extruders, Banbury mixers, kneaders, and mixing rolls to form molding material M. For example, molding material M is extruded from an extruder and chopped into pellets.
[0017] In this embodiment, the additives used include those having a higher elastic modulus and a lower shrinkage rate than the crystalline resin. Since the present invention utilizes the shrinkage difference between the additive and the resin, if the additive deforms in accordance with the shrinking resin when the crystalline resin solidifies, or if the additive shrinks in the same way as the resin, no difference in deformation occurs between the additive and the resin.
[0018] The elastic modulus is a value that indicates the rigidity (i.e. hardness) of a material, and is an index of how much the material will distort when a certain stress is applied to the material. The elastic modulus is a fixed value for each material, so for example, it can be determined by making dumbbell test pieces of crystalline resin and additives and performing a tensile test on the dumbbell test pieces. For the elastic modulus of crystalline resin, the specific measurement conditions are described in, for example, JIS K 7161-1 (Plastics - Determination of tensile properties - Part 1) and JIS K 7161-2 (Plastics - Determination of tensile properties - Part 2). For additives such as glass fiber and talc, the measurement conditions are described in, for example, JIS R 3420 (General test method for glass fiber), JGS 2552-2015 (Uniaxial tensile test method for rock), and JGS 2521 (Uniaxial compression test for rock). Generally, the elastic modulus of crystalline resins is about 1 to 9 GPa, while the elastic modulus of minerals such as talc (hydrated magnesium silicate) and glass is at least 10 GPa. Therefore, it can be said that the elastic modulus of talc and glass fiber is higher than that of crystalline resins (i.e., they are less likely to deform).
[0019] The shrinkage rate is the ratio of the dimensions at the melting temperature of the resin to the dimensions at the solidifying temperature of the resin, and is an index showing the degree to which the dimensions change while the temperature of the resin drops from the melting temperature to the solidifying temperature. The shrinkage rate of a crystalline resin is a fixed value for each crystalline resin, so for example, a molded product is molded using a certain injection molding mold T, and it can be calculated as the ratio of the dimensions of the cavity C of the injection molding mold T to the dimensions of the molded product. Specific measurement conditions such as the shape of the cavity C and molding conditions are, for example, those described in JIS K 7152-4 (Plastics - Injection molding test pieces of thermoplastic plastic materials - Part 4: Determination of molding shrinkage rate). For additives such as glass fiber and talc, for example, the dimensions at the melting temperature of the resin and the dimensions at the solidifying temperature of the resin are measured before kneading with the crystalline resin, and the ratio of the measured dimensions is obtained. Thermal expansion coefficients such as linear expansion coefficient and volume expansion coefficient may also be used. Generally, the shrinkage rate of talc and glass fiber is smaller than that of crystalline resin (that is, they are less likely to shrink).
[0020] The combination of the crystalline resin and the additive, and the amount of the additive can be appropriately set according to the application of the molding material M. As an example, for a vehicle bumper, a molding material M is used in which the crystalline resin is polypropylene (PP), the additives are talc and rubber, and the blending ratio of PP:talc:rubber is 60:20:20 when the whole is taken as 100% by weight. As another example, for a vehicle instrument panel, door trim, etc., a molding material M is used in which the crystalline resin is polypropylene (PP), the additives are talc and rubber, and the blending ratio of PP:talc:rubber is 70:15:15 when the whole is taken as 100% by weight. As another example, for a vehicle engine cover, a molding material M is used in which the crystalline resin is polyamide 6 (PA6), the additives are glass fiber and a colorant (master batch), and the blending ratio of PA6:glass fiber:colorant is 85:14:1 when the whole is taken as 100% by weight.
[0021] [Injection mold] In the present invention, in order to mold a molded product having a fine uneven shape like a leather grain pattern by shrinkage of the resin without forming a fine uneven shape on the mold, the surface of the cavity C of the injection molding mold T is processed to form a plurality of fine recesses. The recesses in this embodiment have a bottom surface at the opening side where the molding material M flows in, and are shaped like a pyramid or frustum in which the area of the cross section parallel to the bottom surface decreases as the depth increases. The process by which the recesses form a fine uneven shape on the surface of the molded product will be described below.
[0022] FIG. 2 is a perspective view showing an example of a fine recess formed on the surface of a cavity C of an injection molding die T. FIG. 2A is a perspective view showing a nest Z, which is one of the parts of a die (also called a die having a divided structure; the same applies below) composed of multiple parts. The nest Z has a cylindrical shape, and a plurality of fine recesses are formed by etching in the part Za surrounded by a solid line in FIG. 2, which is the surface of the cavity C. FIG. 2B is a perspective view showing an enlarged view of the recess formed in the part Za. As shown in FIG. 2B, the shape of the recess formed in the nest Z is a regular square pyramid, and the bottom surface of the opening side into which the molding material M flows is a square of 200 μm in length and 200 μm in width. In the recess shown in FIG. 2B, as the depth of the recess increases, that is, toward the tip of the recess, the cross-sectional area of the recess when cut by a plane parallel to the square bottom surface decreases. In the nest Z in FIG. 2, about 6000 recesses of the same shape are formed in the portion indicated by Za, forming a pattern in which recesses of the same shape are repeated multiple times.
[0023] Next, the filling of the molding material M in the recess shown in FIG. 2 will be described with reference to FIG. 3. FIG. 3 is a vertical cross-sectional view of the recess shown in FIG. 2. The lightly hatched portion on the upper side of FIG. 3 shows an injection molding die T having a square pyramid recess, and the darkly hatched portion on the lower side of FIG. 3 shows the molding material M filled in the cavity C. As shown in FIG. 2, the bottom of the recess is a square with 200 μm sides, and as shown in FIG. 3, the depth of the recess is 100 μm. If the molding material M is filled from the bottom of FIG. 3 into the square pyramid recess shown in FIG. 3, the air does not escape from the recess because the recess shown in FIG. 3 does not have an air vent for venting air, and the air is trapped at the tip of the recess (the deep part of the recess). In this way, air is trapped by the molding material M, which is also called an air trap, and in the case of the recess shown in FIG. 3, an air trap AT occurs at the bottom of the recess.
[0024] Since the molding material M does not completely fill the area where the air trap AT has occurred, an area is created in the recess that is not filled with the molding material M. The occurrence of an area in the cavity C that is not filled with the molding material M in this way is also called a short shot. When a short shot occurs, an area is created on the surface of the filled molding material M that does not come into contact with the surface of the cavity C. In the case of molding material M filled as shown in Figure 3, the area that comes into contact with the area in Figure 3 where the air trap AT has occurred does not come into contact with the surface of the cavity C.
[0025] FIG. 4 is used to specifically show the portion of the molded product that does not contact the surface of the cavity C. FIG. 4 is a vertical cross-sectional view of only the molding material M filled in the recess from FIG. 3. The portion that contacts the area where the air trap AT occurs in FIG. 3 is the portion indicated as X in FIG. 4, and this portion X does not contact the surface of the cavity C of the injection molding die T. In contrast, the portion indicated as Y in FIG. 4 is the portion that contacts the surface of the cavity C of the injection molding die T. In other words, as shown in FIG. 4, the surface of the molding material M filled in the recess in FIG. 3 has a portion X that does not contact the surface of the cavity C and a portion Y that contacts the surface of the cavity C.
[0026] The surface state of the molded product at the portion X that does not contact the surface of the cavity C and the portion Y that contacts the surface of the cavity C will be described with reference to Figs. 5A to 5C. Figs. 5A to 5C are enlarged images of the surface of the molded product taken by a scanning electron microscope (SEM) when the molding material M shown in Fig. 4 is viewed in plan. A tabletop microscope, Miniscope (registered trademark) TM3030Plus (manufactured by Hitachi High-Technologies Corporation), was used as the SEM. The molding material M shown in Figs. 5A to 5C is filled into a recess having the same shape as that shown in Figs. 2 to 3, but the composition of the molding material M in each figure is different. Fig. 5A shows a case where molding was performed using only a base resin (e.g., polypropylene), Fig. 5B shows a case where 20% by weight of talc was mixed into the base resin, and Fig. 5C shows a case where 20% by weight of rubber was mixed into the base resin.
[0027] For the part X that does not come into contact with the surface of the cavity C, when the molding material M is only resin (FIG. 5A), fine irregularities were not observed on the surface of the molded product. In contrast, when the molding material M contains 20% by weight of talc in addition to resin (FIG. 5B), fine irregularities were observed on the part X that does not come into contact with the surface of the cavity C. This is because, while the resin shrinks and deforms in the part X that does not come into contact with the surface of the cavity C, talc, which is a mineral, does not shrink or deform significantly, and so the talc acts as a nucleus to form fine irregularities on its own. The shape of these fine irregularities is not a transfer of the shape of the surface of the cavity C of the injection molding mold T, and therefore does not correspond to the shape of the surface of the cavity C. In addition, when the molding material M contains 20% by weight of rubber in addition to resin (FIG. 5C), fine irregularities were not observed on the surface of the molded product, as in the case where the molding material M is only resin (FIG. 5A). This is because rubber has a lower elastic modulus (softer) than talc, and so when the resin shrinks and deforms, the rubber also deforms.
[0028] 5A to 5C, no matter what material is used, the shape of the surface of the cavity C is transferred to the portion Y in contact with the surface of the cavity C. This is because the molten molding material M solidifies in a short time upon contact with the surface of the cavity C of the injection molding die T while maintaining the shape of the surface of the cavity C with which it is in contact.
[0029] Another example is shown in FIG. 6. FIG. 6 is an enlarged image of a longitudinal section of a molded product taken as a secondary electron image of an SEM when a molding material M, which is a mixture of a base resin (e.g., polypropylene), 20% by weight of talc, and 20% by weight of rubber, is filled into a recess having the same shape as that shown in FIGS. 2-3. Among the parts surrounded by solid lines in FIG. 6, the part SF indicates the surface of the molded product, the part TL indicates talc, and the part RB indicates rubber. As shown in FIG. 6, it was confirmed that talc TL and rubber RB of about 1 to 10 μm were scattered in the area close to the surface SF of the molded product. Therefore, the cross-sectional image in FIG. 6 shows that the additive (especially talc) affects the surface condition of the molded product. The same SEM as that used to take FIGS. 5A-5C was used to take the image in FIG. 6.
[0030] 5A to 5C and 6, it was found that a molded product having a fine uneven surface can be molded without forming fine uneven surfaces on the surface of the cavity C of the injection molding die T by intentionally causing a short shot due to an air trap using a recess in which the opening side into which the molding material M flows is the bottom surface and the area of the cross section parallel to the bottom surface decreases as the depth increases. In other words, by utilizing the shrinkage of the resin and the shrinkage difference between the resin and the additives, a molded product having a fine uneven surface can be stably molded using an injection molding die T with a relatively simple structure.
[0031] The shape of the recess is not limited to those shown in Figs. 2 and 3, and is not particularly limited as long as it is a pyramid or a frustum in which a short shot due to an air trap occurs in the recess, and the pyramid may be a pyramid including a quadrangular pyramid, and the frustum may be a pyramid including a quadrangular pyramid. For example, the maximum length of the base of the pyramid or the frustum is, for example, 200 to 400 µm, may be 250 to 350 µm, or may be 300 to 350 µm in the flow direction in which the molding material M flows in the cavity C. On the other hand, the depth of the pyramid or the frustum in the direction perpendicular to the flow direction of the molding material M can be set to an appropriate value within a range in which the molding material M filled in the recess becomes an undercut and inhibits mold release when the molded product is released from the injection molding die T, and may be, for example, 5 to 150 µm, may be 5 to 100 µm, or may be 10 to 100 µm.
[0032] In order to prevent short shots caused by air traps in the recesses, the ratio of the maximum length of the bottom surface to the depth is 1:1 to 5:1, preferably 2:1 to 4:1, in terms of "maximum length of bottom surface: depth". This is because, if the maximum length of the bottom surface is small and the depth is deep, the molding material M, which has high viscosity, cannot enter the recesses, resulting in a state equivalent to the recesses not being provided. Conversely, if the maximum length of the bottom surface is large and the depth is shallow, the molding material M fills most of the recesses, resulting in a state equivalent to the portion X of the cavity C that does not come into contact with the surface of the cavity C not being generated.
[0033] When the maximum length of the bottom surface is 200 to 400 μm in the flow direction, the depth that satisfies the ratio of 1:1 to 5:1 in the "maximum length of the bottom surface: depth" is 40 to 400 μm, and the depth that satisfies the ratio of 2:1 to 4:1 in the "maximum length of the bottom surface: depth" is 50 to 200 μm. However, it is preferable that the depth is 150 μm or less so that the molding material M filled in the recess does not hinder the mold release. Therefore, the depth of the recess is set to a maximum of 150 μm. In this case, when the maximum length in the flow direction is 200 μm, the ratio of the "maximum length of the bottom surface: depth" is 1.34:1 (200÷150=1.33···). The depth of the recess can be set in the same manner when the maximum length of the bottom surface in the flow direction is 250 to 350 μm and when it is 300 to 350 μm. The depth of the recess may also be set to a maximum of 100 μm.
[0034] In addition, since the flow direction of the molding material M in the cavity C changes depending on the position of the gate 17, it is preferable that the shape of the recess is symmetrical in at least one of the vertical and horizontal directions when viewed from above so that a short shot due to an air trap does not occur regardless of the direction from which the molding material M is filled. For example, it is line-symmetrical with respect to a line in the vertical direction and a line in the horizontal direction when viewed from above, and as another example, it is point-symmetrical with respect to the center of gravity of the bottom surface.
[0035] Examples of recesses different from those shown in Figs. 2-3 are shown in Figs. 7A and 8A. Fig. 7A is a vertical cross-sectional view of a recess different from that shown in Fig. 3. The recess shown in Fig. 7A is a square pyramid shape, and the bottom surface of the opening side into which the molding material M flows is a square of 300 μm in length and 300 μm in width, and the depth of the recess is 100 μm. The lightly hatched portion on the upper side of Fig. 7A shows an injection molding die T having a recess of a square pyramid, and the darkly hatched portion on the lower side of Fig. 7A shows the molding material M filled in the cavity C. If the molding material M is filled from the lower side of Fig. 7A into the recess of the square pyramid shown in Fig. 7A, an air trap AT is generated at the bottom of the recess as shown in Fig. 7A.
[0036] Fig. 7B is a vertical cross-sectional view of only the molding material M filled in the recess from Fig. 7A. The part in contact with the area where the air trap AT occurred in Fig. 7A is the part indicated as X in Fig. 7B, and this part X does not contact the surface of the cavity C of the injection molding die T. In contrast, the part indicated as Y in Fig. 7B is the part in contact with the surface of the cavity C of the injection molding die T. In other words, similar to the case shown in Fig. 4, the surface of the molding material M filled in the recess in Fig. 7A has a part X that does not contact the surface of the cavity C and a part Y that contacts the surface of the cavity C.
[0037] The shape of the recess shown in Fig. 8A is that of a truncated square pyramid, the bottom surface of the opening side into which the molding material M flows is a square of 400 μm in length and 400 μm in width, and the depth of the recess is 100 μm. The lightly hatched portion on the upper side of Fig. 8A indicates an injection molding die T having a recess of a truncated square pyramid, and the darkly hatched portion on the lower side of Fig. 8A indicates molding material M filled in cavity C. If molding material M is filled from the lower side of Fig. 8A into the recess of the truncated square pyramid shown in Fig. 8A, an air trap AT will be generated at the bottom of the recess, as shown in Fig. 8A.
[0038] Fig. 8B is a vertical cross-sectional view of only the molding material M filled in the recess from Fig. 8A. The part in contact with the area where the air trap AT occurred in Fig. 8A is the part indicated as X in Fig. 8B, and this part X does not contact the surface of the cavity C of the injection molding die T. In contrast, the part indicated as Y in Fig. 8B is the part in contact with the surface of the cavity C of the injection molding die T. In other words, similar to the case shown in Fig. 4, the surface of the molding material M filled in the recess in Fig. 8A has a part X that does not contact the surface of the cavity C and a part Y that contacts the surface of the cavity C.
[0039] Here, the shape of the recess shown in Figs. 2-3 is referred to as Shape A, the shape of the recess shown in Fig. 7A is referred to as Shape B, and the shape of the recess shown in Fig. 8A is referred to as Shape C. Comparing Shape A, Shape B, and Shape C, the ratio of the maximum length of the bottom surface to the depth in each shape, in terms of "maximum length of bottom surface:depth", is 2:1 for Shape A, 3:1 for Shape B, and 4:1 for Shape C. Comparing Shape B and Shape C, both are square pyramid shapes with the same height, but Shape C has a larger bottom surface than Shape B and is closer to a rectangular parallelepiped, and therefore the air trap AT portion is smaller in Shape C than in Shape B.
[0040] The shape of the recess may be set by the skewness (Rsk) defined by the following formula.
[0041]
number
[0042] Skewness is one of the feature average parameters in the height direction that indicates the deviation of the surface unevenness from the average line. The cube mean of Z(x) at the reference length lr is calculated as the root mean square height Rq 3 The skewness is non-dimensionalized by dividing by the cube of . A detailed definition of skewness is described in JIS B 0601 (Geometrical Product Specifications (GPS)-Surface Texture: Profile Curve Method-Terminology, Definitions and Surface Texture Parameters) and the like. In a shape such as a recess, the skewness value is a negative value, with the skewness value of Shape A being -1.29, the skewness value of Shape B being -1.84, and the skewness value of Shape C being -2.60. The skewness value of the recess in this embodiment is, for example, within the range of -1.0 to -3.0.
[0043] The injection molding method and the injection mold according to the present embodiment have been described so far, but the injection molding method and the injection mold according to the present invention can be widely applied to general injection molding regardless of the size of the molded product. The fine uneven shape on the surface molded by the injection molding method and the injection mold according to the present invention has the same effect as the grain (wrinkles) of leather grain pattern, so that a molded product with a high texture and matte (low gloss) surface can be obtained without painting. Examples of application of this molding method include not only interior parts of a vehicle such as steering wheels, instrument panels, and door trims, but also exterior parts such as bumpers, engine covers, door mirror housings and wheel caps, and mechanical parts such as air intake manifolds. EXAMPLES
[0044] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to these examples.
[0045] 1.Injection mold A molded product having a fine uneven surface was molded using an injection mold T having a cavity C shown in FIG. 9A as a representative flat plate shape. The cavity C shown in FIG. 9A is 320 mm long, 80 mm wide, and 2.5 mm thick, and the molding material M is filled into the cavity C through a runner 16 and a gate 17. The cavity C shown in FIG. 9A has a portion 300 mm from the gate 17 into which a 20 mm diameter insert Z is fitted, and a pattern in which the same shaped recesses are repeated multiple times is formed on the surface of the insert Z over a square range of 13 mm long and 13 mm wide. Three types of insert Z were prepared: one with an A-shaped pattern shown in FIG. 9B, one with a B-shaped pattern, and one with a C-shaped pattern. As described above, the A-shaped corresponds to the recesses shown in FIGS. 2-3, the B-shaped corresponds to the recesses shown in FIG. 7A, and the C-shaped corresponds to the recesses shown in FIG. 8A.
[0046] The processing of the pattern on the insert Z was a combination of ultra-precision cutting and electroforming. That is, a master mold having a shape corresponding to the pattern was produced by ultra-precision cutting, and the pattern was formed on the surface of the insert Z by nickel electroforming using the master mold. The obtained injection molding die T was processed with an accuracy of ±3 μm or less from the design value.
[0047] 2.Molding material The molding material M used was a polypropylene-based material containing 20% by weight of talc and 20% by weight of rubber as additives. NEWCON NBX03HRS (manufactured by Japan Polypropylene Corporation) was used as the polypropylene. The physical properties of the polypropylene used and the method of measuring them are shown in FIG. 10A. MAT-725TP (manufactured by Shiraishi Calcium Co., Ltd.) was used as the talc. LC170 (manufactured by LG Chem, Ltd.) was used as the rubber, which is an elastomer that can be commonly used as an additive to add impact resistance to resin. These materials were melt-kneaded by a twin-screw extruder and processed into pellets.
[0048] In particular, there are several specifications for talc with different average particle diameters within the range of approximately 1 to 15 μm, but in this embodiment, those with an average particle diameter of 4.0 μm, 6.5 μm, and 9.3 μm were used as shown in Fig. 10B. That is, the molding material M used in this embodiment is four types: polypropylene only, polypropylene to which talc and rubber with an average particle diameter of 4.0 μm are added at 20% by weight, polypropylene to which talc and rubber with an average particle diameter of 6.5 μm are added at 20% by weight, and polypropylene to which talc and rubber with an average particle diameter of 9.3 μm are added at 20% by weight.
[0049] The particle size distribution of the talc shown in Fig. 10B was obtained by measuring the particle size distribution by a wet method using a laser diffraction particle size distribution measuring device MASTERSIZER 3000 (manufactured by Malvern Instruments Ltd.). A 0.2 wt% aqueous solution of sodium hexametaphosphate was used as the dispersion medium, and an ultrasonic homogenizer US-300 (manufactured by Nippon Seiki Seisakusho Co., Ltd.) was used for dispersion. The ultrasonic homogenizer was used for one minute at an oscillation frequency of 19.5 kHz and a current of 300 μA (output of 0.03 W).
[0050] FIG. 10C shows the results of an analysis of the melt viscosity of the molding material M in order to analyze the effect of the addition of talc with different particle sizes on the molding material M. The horizontal axis of the graph in FIG. 10C is the angular frequency, and the vertical axis is the viscosity of the molten molding material M. The angular frequency can also be interpreted as the shear rate. Such melt viscosity for each angular frequency is measured using a capillary rheometer, for example, according to the method described in JIS K7199 (Plastics - Test method for flow characteristics of plastics using capillary rheometer and slit die rheometer). In this example, the viscosity was measured for angular frequencies of 0.1 to 100 rad / s using MCR301 (manufactured by Anton Paar Corp.) as a viscoelasticity analyzer, under conditions of a temperature of 230°C and a strain of 10% in a nitrogen atmosphere.
[0051] Near the surface of the cavity C, the molten molding material M begins to cool and solidify by the injection mold T, so the speed at which the molding material M flows decreases. Therefore, it is the viscosity characteristics of the low frequency region (i.e., the region with low shear rate) that affect the transfer of the fine shape formed on the surface of the cavity C. Therefore, the low frequency range enclosed by the square is particularly noted and enlarged. As shown in the lower part of Figure 10C, it was confirmed that the viscosity of the molding material M to which talc was added was increased compared to the melt viscosity of the base polypropylene alone. On the other hand, the effect of the difference in the average particle size of talc on the viscosity was not confirmed. Therefore, it can be said that the fluidity of the molding material M is slightly reduced by adding talc, but the fluidity of the molding material M hardly changes even if the average particle size of talc is changed.
[0052] 3. Molding conditions In this embodiment, the injection molding machine used was FN2000-25A (manufactured by Nissei Plastics Co., Ltd.), which is a 110t class injection molding machine. The maximum injection speed of the injection molding machine was 100mm / s, the maximum injection pressure was 220MPa, the mold clamping force was 1098kN, and the screw diameter was 35mm. In addition, the molding conditions were set to the injection speed of 50mm / s, the injection time of 1 second, the dwell pressure of 20MPa, the dwell time of 10 seconds, the resin temperature of 200°C, and the mold temperature of 40°C, assuming molding conditions for general automotive resin parts. By performing injection molding using the injection molding machine under the above molding conditions, it was possible to obtain a desired molded product without causing molding defects.
[0053] So far, the injection molding die T, molding material M, and molding conditions of this example have been described. Next, the molded product obtained in this example will be described.
[0054] [Fine unevenness of molded products] FIG. 11 is an enlarged image of the surface of a molded product showing the state of filling of the molding material M in the recesses of shapes A, B, and C when the molding material M is filled in the injection molding mold T shown in FIG. 9 under the above conditions. The images shown in FIG. 11 are enlarged images of the surfaces of the molded products when the above-mentioned four types of molding material M are filled for each of shapes A, B, and C, using a laser microscope LEXT OLS4100 (manufactured by Olympus Corporation). As for the recesses of shape A, as shown in the four images in the first row of the table in FIG. 11, it was confirmed that the addition of talc forms fine irregularities on the surface of the molded product, and that the number of fine irregularities increases by increasing the particle size of talc, making the surface of the molded product rougher.
[0055] For the B-shaped recess, it was confirmed that, as with the A-shaped recess, the addition of talc formed fine unevenness on the surface of the molded product, and that the number of fine unevenness increased by increasing the particle size of the talc, making the surface of the molded product rougher. Specifically, this is shown in the four images in the second row of the table in FIG. 11. On the other hand, for the C-shaped recess, as shown in the four images in the third row of the table in FIG. 11, it was confirmed that the addition of talc formed fine wrinkle patterns on the surface of the molded product. The shape of this wrinkle pattern was more complex and fine than the fine unevenness generated by talc with a small average particle size (for example, the unevenness formed by the A-shaped recess). It was also confirmed that the number of wrinkles increased by increasing the particle size of the talc. In this way, it was confirmed that by using the injection molding mold T having the recess of this embodiment, a molded product having fine unevenness such as a leather grain pattern can be molded without forming fine unevenness on the surface of the cavity C of the injection molding mold T.
[0056] [Fine wrinkles on the surface of the molded product] In order to clarify the mechanism by which the fine wrinkle pattern on the surface of the molded product confirmed in the case of the C-shaped recess shown in FIG. 11 occurs, the conditions of the dwell pressure among the above-mentioned molding conditions were changed to confirm how the surface state of the molded product changed. Specifically, in the case where the molding material M made of polypropylene to which talc having an average particle size of 9.3 μm and rubber were added at 20% by weight each was filled into the injection molding mold T using the insert Z having the C-shaped recess pattern (the case in the lower right of FIG. 11), the dwell pressure was changed to 0 MPa, 5 MPa, 10 MPa, and 20 MPa. Images showing the surface state of the molded product at each dwell pressure are shown in FIG. 12. The upper image in FIG. 12 is an enlarged image showing the surface state of the molded product when the recess is viewed obliquely, and the upper image in FIG. 12 is an enlarged image showing the surface state of the molded product when the recess is viewed in plan.
[0057] When the holding pressure was 0 MPa, the filled molding material M was not subjected to sufficient pressure, and a short shot occurred in the cavity C. In addition, in the flow direction of the molding material M, as shown by the arrow in FIG. 12, it was confirmed that the side of the C-shaped recess was transferred to the molded product on the side closer to the filling end of the molding material M (the side farther from the gate 17). In contrast, in the flow direction of the molding material M, it was confirmed that the shape of the C-shaped recess was not transferred to the molded product on the side farther from the filling end of the molding material M (the side closer to the gate 17). In addition, depressions of a shape similar to the wrinkle pattern formed by the contraction of polypropylene in the molding material M were confirmed. This is because, while the molding material M solidifies in a short time on the side farther from the filling end of the molding material M, the solidification of the molding material M is delayed in the center of the recess, and wrinkles are formed due to the contraction of polypropylene so that the center is depressed while leaving the side portions.
[0058] When the dwell pressure was 5 MPa and 10 MPa, the pressure applied to the filled molding material M increased, and the area of the recessed shape that was transferred to the surface of the molded product expanded. In addition, it was confirmed that when the dwell pressure was in the range of 5 to 10 MPa, repeated wrinkles were formed, such as the fine wrinkle pattern shown in Figure 11. This is because the wrinkles formed in the recesses when the dwell pressure was 0 MPa were compressed in the flow direction by the flowing molding material M, and the wrinkles formed in the recesses were folded. In addition to this, the shrinkage of polypropylene acts, causing differences in the distribution of talc inside the folded wrinkles, and the difference in talc concentration also has an effect, causing differences in shrinkage.
[0059] In addition, when the dwell pressure is 20 MPa, it was confirmed that fine wrinkle patterns were formed on the surface of the molded product as shown in FIG. 11. The generation of such wrinkle patterns was confirmed when the ratio of the maximum length of the bottom surface to the depth, in terms of "maximum length of bottom surface: depth", was within the range of 3.5:1 to 4.5:1. The generation of wrinkle patterns was also confirmed when the value of the skewness of the recess was within the range of -2.0 to -3.0. The generation of wrinkle patterns was also confirmed when the maximum length of the bottom surface of the pyramid and frustum was within the range of 350 to 450 μm and the depth of the recess was 80 to 120 μm. As in the case of a C-shaped recess, the processing of the surface of the cavity C becomes easier as the cross-sectional area of the tip portion (deep portion) of the recess increases, so that the above-mentioned shape of the recess has an advantageous effect in that a complex uneven shape (wrinkle pattern) can be formed without complex processing of the injection molding die T.
[0060] [Cross section of molded product] In order to confirm the state of the talc and rubber in the molded product, the molded product was molded using the A-shaped pattern nest Z, and enlarged images of the longitudinal section of the molded product were obtained using a scanning electron microscope (SEM). The obtained images are shown in Figs. 13A to 13D. The SEM used was the same as that used for taking the images of Figs. 5A to 5C. In the molded products of Figs. 13A and 13B, the molding material M used was polypropylene to which 20% by weight of talc and rubber having an average particle size of 4.0 μm were added, and in the molded products of Figs. 13C and 13D, the molding material M used was polypropylene to which 20% by weight of talc and rubber having an average particle size of 9.3 μm were added. In addition, Figs. 13A and 13C are enlarged images of the part near the surface of the molded product (the so-called skin layer), and Figs. 13B and 13D are enlarged images of the part near the center in the thickness direction of the molded product (the so-called core layer).
[0061] First, a molded product using a molding material M obtained by adding 20% by weight each of talc having an average particle size of 4.0 μm and rubber to polypropylene as shown in FIGS. 13A and 13B will be described. In FIG. 13A, among the parts surrounded by solid lines, the SF part indicates the surface of the molded product, the TL part indicates talc, and the RB part indicates rubber. In FIG. 13B, among the parts surrounded by solid lines, the TL part indicates talc, and the RB part indicates rubber. As shown in the enlarged images of FIGS. 13A and 13B, it was confirmed that the talc TL and the rubber RB were scattered and dispersed almost uniformly in both the skin layer and the core layer of the molded product. In addition, as shown in FIG. 13A, it was confirmed that the talc TL was scattered even in the part close to the surface SF of the molded product, and a fine uneven shape was formed with the talc TL as a core.
[0062] Next, a molded product using a molding material M obtained by adding 20% by weight each of talc having an average particle size of 9.3 μm and rubber to polypropylene as shown in FIGS. 13C and 13D will be described. In FIG. 13C, among the parts surrounded by solid lines, the SF part indicates the surface of the molded product, the TL part indicates talc, and the RB part indicates rubber. In FIG. 13D, among the parts surrounded by solid lines, the TL part indicates talc, and the RB part indicates rubber. As shown in the enlarged images of FIGS. 13C and 13D, it was confirmed that the talc TL and the rubber RB were scattered and dispersed almost uniformly in both the skin layer and the core layer of the molded product. In addition, as shown in FIG. 13C, it was confirmed that the talc TL was scattered even in the part close to the surface SF of the molded product, and a fine uneven shape was formed with the talc TL as a core.
[0063] In particular, when comparing Figures 13A and 13C, it was confirmed that the talc TL shown in Figure 13C has a larger particle size than the talc TL shown in Figure 13A, and therefore contributes more to the formation of fine irregularities on the surface SF of the molded article. In other words, it was confirmed that the larger the average particle size of the talc TL, the more fine irregularities are formed on the surface SF of the molded article, the deeper the concaves of the irregularities are, and the higher the height of the convexities of the irregularities is. In addition, from the observation of the longitudinal section of the same molded article, it was confirmed that when the average particle size of the talc TL exceeds approximately 7.5 μm, the contribution of the talc TL to the formation of fine irregularities on the surface SF of the molded article becomes significant.
[0064] [Glossiness of molded product] To confirm the effect of the fine unevenness formed on the surface of a molded product on the appearance of the product, the glossiness of each of the molded products shown in Figure 11 was measured. Glossiness is a numerical value that is an index of glossiness, which is the ratio of the intensity of incident light to that of specularly reflected light when a certain object is irradiated with light. Specular reflected light refers to reflected light with the same angle of incidence and reflection. If the surface is smooth, the proportion of specular reflected light is high and the glossiness value is high, but if the surface is rough, the light is reflected in various directions, so the glossiness value is low. In other words, if the surface of a molded product is smooth and does not have fine unevenness, the glossiness value is high and a glossy texture is obtained. In contrast, if the surface of a molded product has fine unevenness, the surface of the molded product becomes rough, so the glossiness value is low and a matte texture is obtained. Note that a glossy texture leads to a shiny surface of the molded product, so a matte texture can create a sense of luxury.
[0065] The glossiness is measured, for example, according to the method described in JIS Z 8741 (Specular Glossiness-Method of Measurement). In this embodiment, a GM-268 Plus (manufactured by Konica Minolta, Inc.) was used as a glossmeter, the glossiness measurement angle was set to 60°, and the measurement area was set to 2 mm x 4 mm, and the glossiness was measured. The measurement results of the glossiness are shown in the graph of FIG. 14. The horizontal axis of the graph of FIG. 14 indicates the value of the skewness of the recess, and the vertical axis indicates the glossiness of the surface of the molded product. In the graph of FIG. 14, the glossiness value (right side of the graph) when the recess is shaped A, the glossiness value (center of the graph) when the recess is shaped B, and the glossiness value (left side of the graph) when the recess is shaped C are plotted for each of the four types of molding materials M. From the measurement results shown in the graph of FIG. 14, it was confirmed that the glossiness of the surface of the molded product decreases as the skewness value of the recess increases. In other words, it was confirmed that the smaller the size of each recess, the lower the glossiness value and the matte texture can be obtained. In contrast, it was confirmed that in a concave portion with a large flat surface, such as a C-shape, the specular reflection of light is greater, resulting in a higher gloss value.
[0066] On the other hand, when comparing the molding material M made of only polypropylene with the molding material M to which talc was added, it was confirmed that the gloss value was lower when talc was added to the molding material M. It was also confirmed that the gloss value was lower when the average particle size of talc was increased. In particular, the gloss value of the C-shaped recess was significantly reduced by increasing the average particle size of talc. This is due to the diffuse reflection of light caused by the fine wrinkle pattern formed on the surface of the molded product as shown in Figure 12. In other words, it was found that by forming a fine wrinkle pattern on the surface of the molded product, it is possible to mold a molded product having a matte surface with a low gloss value while using a pattern having a relatively simple shape such as a C-shape.
[0067] In the past, gloss was controlled by changing the fine irregularities on the surface of cavity C in injection molding die T and transferring that shape accurately. In contrast, in the present invention, gloss can be changed and controlled by changing the fine irregularities on the surface of the molded product by changing the shape of the recesses in cavity C and the addition of talc (particularly the average particle size of talc).
[0068] [Talc added amount] In order to confirm the effect of the amount of talc added on the surface condition of the molded product, a number of nests Z with different glossiness were prepared, and molded products were formed using the prepared nests Z in an injection molding die T, and the glossiness of each molded product was measured. In this example, ten types of nests Z (A-01 to A-10) with different glossiness, as shown in FIG. 15A, were prepared. An oblique image of each nest Z is shown in FIG. 15B. In FIG. 15B, there is a square part with different surface properties in the center of each nest Z, and this part is processed, and the glossiness of the processed part in each nest Z is different. In FIG. 15B, the number next to each nest Z is the glossiness value.
[0069] FIG. 15C is a plan view showing an enlarged processed portion of the insert Z of A-01. In this embodiment, the surface of the mold was subjected to etching including masking, followed by sandblasting and glass blasting to produce a surface with the properties shown in FIG. 15C. When sandblasting is performed on an etched surface, the glossiness of the surface decreases. In contrast, when glass blasting is performed on an etched surface, the glossiness of the surface increases. In this way, the glossiness of the processed portion can be adjusted by combining sandblasting and glass blasting. The glossiness of the processed portion was measured using the same gloss meter as described above under the same conditions.
[0070] As the molding material M, NEWCON NBX03HRS (manufactured by Japan Polypropylene Corporation) having the physical properties shown in Fig. 10A, MAT-725TP (manufactured by Shiraishi Calcium Co., Ltd.) having an average particle size of 4.0 μm and LC170 (manufactured by LG Chem, Ltd.) shown in Fig. 10B were melt-kneaded in a twin-screw extruder to form pellets. The talc content was changed to five values: 0 wt%, 5 wt%, 10 wt%, 15 wt%, and 20 wt%. The molding conditions were the same as those described in "3." above.
[0071] For the molded products obtained for each of the inserts Z, the gloss of the part where the processed part was transferred was measured under the same conditions using the same gloss meter as described above. The measurement results of the gloss are shown in FIG. 15D. The horizontal axis of FIG. 15D indicates the amount of talc added (wt%), and the vertical axis indicates the gloss of the molded product surface (%). (For the relationship between the plotted marks and the inserts Z, refer to the legend on the right side of FIG. 15D.) As shown in FIG. 15D, it was confirmed that the gloss of the molded product obtained decreased as the amount of talc added increased in the range of 15 wt% or less. In contrast, it was confirmed that the gloss of the molded product did not change significantly even if the amount of talc added increased in the range of 15 wt% or more. This tendency was true for any of the inserts Z A-1 to A-10, and the gloss value of the molded product obtained was 1.3 to 1.6 when the amount of talc added exceeded 15 wt% regardless of the insert Z used. 15D, it was confirmed that the gloss value can be sufficiently reduced by adding 15% by weight or more of talc to the crystalline resin. In the molding material M of this embodiment, about 5 to 40% by weight of talc can be added to the crystalline resin, but in order to obtain a molded product having a matte surface texture using the injection molding die T according to the present invention, it is preferable to add 15% by weight or more of talc to the crystalline resin.
[0072] [Water-repellent effect due to fine unevenness] In order to confirm the water-repellent effect due to the shape of the fine wrinkle pattern on the surface of the molded article confirmed in the case of the C-shaped recess shown in Figures 11 and 12, the contact angle was measured by the sessile drop method for the molded article molded using the nest Z having the C-shaped recess pattern. The method for measuring the contact angle by the sessile drop method is described, for example, in JIS K6768 (Plastics - Films and Sheets - Wetting Tension Test Method). In this example, a DM501 (manufactured by Kyowa Interface Science Co., Ltd.) was used as a contact angle meter, the volume of the droplet was set to 5 μl, and the contact angle was measured by the tangent method. When making the droplet, a mixed liquid prepared according to JIS K6768 was used, but in this example, water (purified water, wetting tension: 73.0 mN / m) was used. The larger the contact angle of the droplet, the less likely the surface of the molded article is to become wet, and the higher the water repellency. On the other hand, the smaller the contact angle of the droplet, the more likely the surface of the molded article is to become wet, and the lower the water repellency.
[0073] The upper part of the table in FIG. 16 shows an enlarged image showing the state of the surface of the molded product in the C-shaped recess for each molding material M, and the lower part shows an enlarged image of a droplet dropped on the surface of each molded product and the contact angle. As shown in FIG. 16, it was confirmed that the contact angle of the droplet increases by adding talc to the molding material M. It was also confirmed that the larger the average particle size of the talc, the larger the contact angle of the droplet. In other words, it was confirmed that the water repellency of the surface of the molded product is improved by adding talc, and the larger the average particle size of the added talc, the greater the water repellency effect obtained. This is because the surface tension of water increases due to the inclusion of air in the fine uneven shape.
[0074] In order to evaluate the water repellency in more detail, in addition to the contact angle by the sessile drop method described above, the advancing contact angle and receding contact angle were measured for each molded product shown in FIG. 11 using the same contact angle meter. The difference is that the contact angle by the sessile drop method is a static contact angle, whereas the advancing contact angle and the receding contact angle are dynamic contact angles. The advancing contact angle and the receding contact angle are explained with reference to FIG. 17A. The advancing contact angle and the receding contact angle are contact angles when the droplet D tries to roll and slide in the direction of the arrow Aa due to gravity when the flat plate P is tilted with a water droplet D placed on it. The contact angle θ1 between the flat plate P and the direction in which the droplet D rolls and slides is the advancing contact angle, and the contact angle θ2 between the flat plate P and the opposite side to the direction in which the droplet D rolls and slides is the receding contact angle. In this example, the advancing contact angle was measured by the expansion method, in which the volume of a droplet D placed on a molded product receiver was increased by injecting a sample into the droplet D with a microsyringe, and the receding contact angle was measured by the contraction method, in which the sample was sucked up with the microsyringe and the volume of the droplet D was decreased. Distilled water was used as the sample.
[0075] In this example, water (purified water) was used to create a droplet, and the volume of the droplet was gradually increased from 0 μl to 30 μl over a period of about 3 seconds when determining the advancing contact angle. The measurement results of the advancing contact angle are shown in FIG. 17B. The horizontal axis of FIG. 17B indicates the volume of the droplet D, and the vertical axis indicates the contact angle. As shown in FIG. 17B, it was confirmed that there was a large amount of noise regarding the advancing contact angle, and there was no significant difference between the molding materials M. This is due to the fact that the advancing contact angle changes significantly when the droplet D starts to slide from a stationary state.
[0076] Next, the measurement results of the receding contact angle are shown in FIG. 17C. In this embodiment, when determining the receding contact angle, the volume of the droplet was gradually reduced from 30 μl to 0 μl over about 3 seconds. The horizontal axis of FIG. 17C indicates the volume of the droplet D, and the vertical axis indicates the contact angle. As shown in FIG. 17C, it was confirmed that the receding contact angle was larger in the case of the molding material M containing only polypropylene, compared with the molding material M containing only polypropylene. It was also confirmed that the receding contact angle was larger as the average particle size of the added talc was increased. This is because the surface tension of water was increased by the inclusion of air in the fine uneven shape. In addition, the receding contact angle did not show any noise like the advancing contact angle. This is because when the droplet D starts to slide from a stationary state, the shape of the droplet D is greatly deformed in the direction in which the droplet D rolls and slides, whereas the shape of the droplet D is not so greatly deformed on the opposite side of the direction in which the droplet D rolls and slides.
[0077] Furthermore, FIG. 17D shows the hysteresis of the contact angle calculated by subtracting the receding contact angle shown in FIG. 17C from the advancing contact angle shown in FIG. 17B. When the hysteresis is small, the advancing contact angle θ1 and the receding contact angle θ2 in FIG. 17A are close to each other, which indicates that the shape of the droplet D sliding on the flat plate P is not deformed much. In other words, the droplet D can move relatively freely as if sliding on the flat plate P, and the water repellency of the flat plate P is high. On the other hand, when the hysteresis is large, the advancing contact angle θ1 in FIG. 17A is relatively larger than the receding contact angle θ2, which indicates that the shape of the droplet D sliding on the flat plate P is crushed and deformed. In other words, the droplet D cannot easily move on the flat plate P, and the water repellency of the flat plate P is low.
[0078] As shown in FIG. 17D, it was confirmed that the hysteresis value was smaller in the case of the molding material M containing only polypropylene when talc was added. It was also confirmed that the hysteresis value was smaller as the average particle size of the added talc increased. This is because the surface tension of water was increased by the inclusion of air in the fine unevenness. In this way, it was confirmed that the fine unevenness molded using the injection molding mold T having the recesses of this embodiment imparts static and dynamic water repellency to the molded product.
[0079] [Scratch resistance due to fine unevenness] In order to confirm the effect of the fine unevenness formed on the surface of the molded product on the scratch resistance of the product, a scratch test was performed on each of the molded products shown in FIG. 11, and a quantitative evaluation of the scratch resistance was performed based on the difference between the color measured before the scratch test and the color measured after the scratch test. In this example, a Revetest Scratch Tester (S / N: 27-486) (manufactured by CSM Instruments) was used as a scratch tester. The scratch test was performed using a diamond indenter (N05-3887) with a tip curvature radius of 50 μm. The indenter was moved at a moving speed of 10 mm / sec with a load of 10 N. For each molded product, the indenter was moved three times for each molded product at intervals of 2 mm. An enlarged image of the surface of each molded product after the scratch test is shown in FIG. 18A. The image in FIG. 18A was taken using the same laser microscope as that used to obtain the image in FIG. 11.
[0080] In this example, in order to calculate the change in color of the molded product before and after the scratch test, the L * The value was measured. * The value represents the brightness of the color and ranges from 0 to 100. * The lower the value, the lower the lightness. * A higher value indicates a higher brightness. * Colors with low values are close to black, and L * A color with a high value is close to white. *The L value is measured, for example, according to the method described in JIS Z 8781-4 (Colorimetry-Part 4: CIE 1976 L*a*b* color space). In this example, the L value was measured using a spectrophotometer (CM-3700A: manufactured by Konica Minolta, Inc.) before and after the scratch test. The measurement range was 3 mm x 5 mm.
[0081] When a scratch test like that shown in Figure 18A is performed, the molded product reflects light in a certain direction, so the surface of the molded product appears white. In other words, when the surface of the molded product is scratched and turns white, the measured L * The value becomes higher. L after scratch test * If the rate of change in the value is smaller, the scratch is less noticeable. * To make the values easier to measure, a black master batch was added to molding material M to give the molded product a black color.
[0082] Measured L * The rate of change in the value is shown in FIG. 18B. The horizontal axis of FIG. 18B is the L * The vertical axis shows the L value before and after the scratch test. * The change in the value is shown. For molded products made with molding material M, which is made of polypropylene only, the change in the value is shown in Fig. 1. * The values were significantly different, so they were not plotted in the graph of FIG. 18B. As shown in FIG. 18B, the L * The lower the value and the closer the color of the molded product is to black, the greater the L * It was confirmed that the rate of change in the value becomes higher. That is, as shown in Figure 14, the smaller the size of each concave portion, such as the A-shaped concave portion, the lower the gloss value and a matte texture is obtained, but scratches on the surface are easily noticeable. In contrast, in the case of a C-shaped concave portion with a large flat surface, the specular reflection of light becomes large, and although the gloss value is not as low as that of the A-shaped concave portion, scratches on the surface are less noticeable.
[0083] In addition, regardless of the shape of the concaves, if fine concaves and convexes are formed on the molded product, scratch resistance is imparted. The larger the average particle size of the added talc, the greater the L of the surface of the molded product.* The value becomes lower (i.e., blacker), and the L * It was also confirmed that the rate of change in the value was smaller. In other words, it was found that adding talc with a large average particle size to molding material M improves the scratch resistance of the surface of the molded product. This is because the larger the particle size of the talc, the more the number of fine irregularities increases, suppressing the effect of light reflection in a certain direction due to scratches.
[0084] In particular, the improvement in scratch resistance was remarkable for the C-shaped recesses that formed fine wrinkle patterns on the surface of the molded product. As shown in the enlarged image of the molded product after the scratch test in Figure 18C, in the molded product molded using the insert Z having the C-shaped recess pattern, some of the fine wrinkle patterns on the surface of the molded product remained even after the scratch test, and the remaining uneven shape was L. * This is because the change in the value was suppressed. In this way, it was confirmed that the fine uneven shape molded using the injection molding mold T having the recesses of this embodiment imparts scratch resistance to the molded product.
[0085] [Embodiments of the present invention] As described above, according to the present embodiment, there is provided an injection molding method in which a molding material M containing a crystalline resin and an additive having a higher elastic modulus and a lower shrinkage rate than the crystalline resin is filled into a mold having a cavity C with a plurality of recesses on the surface thereof, the recesses being formed in a cone or frustum shape with the bottom surface being at the opening side into which the molding material M flows, and the area of the cross section parallel to the bottom surface decreasing as the depth increases, the maximum length of the bottom surface in the flow direction of the molding material is 200 to 400 μm, the depth of the cone or frustum in the direction perpendicular to the flow direction is 40 to 150 μm, and the ratio of the maximum length of the bottom surface to the depth is 1.34:1 to 5:1. This makes it possible to mold a molded product having a fine uneven shape without forming a fine uneven shape on the mold.
[0086] Furthermore, according to the injection molding method of this embodiment, the depth is 50 to 150 μm, and the ratio of the maximum length of the bottom surface to the depth is 2: 1 to 4: 1. This makes it possible to more reliably mold a molded product having a fine uneven shape without forming a fine uneven shape on the molding die.
[0087] According to the injection molding method of this embodiment, the recess has a pyramidal or truncated pyramidal shape with the bottom surface being the opening side into which the molding material M flows, and the area of the cross section parallel to the bottom surface decreases as the depth increases. This makes it possible to more reliably mold a molded product having a finely uneven shape regardless of the flow direction of the molding material M.
[0088] According to the injection molding method of this embodiment, the recess has a quadrangular pyramid or truncated quadrangular pyramid shape with the bottom surface being the opening side into which the molding material M flows, and the area of the cross section parallel to the bottom surface decreases as the depth increases. This makes it possible to more reliably mold a molded product having a finely uneven shape regardless of the flow direction of the molding material M.
[0089] According to the injection molding method of this embodiment, the surface of the cavity is processed to have a pattern in which the same shaped recesses are repeated multiple times, which makes it possible to mold a molded product having a fine uneven shape like a leather grain pattern without processing the surface of the cavity C to form a fine uneven shape.
[0090] According to the injection molding method of the present embodiment, the crystalline resin is polypropylene, the additive is talc, and the molding material M further contains rubber. This makes it possible to impart impact resistance to the molded product.
[0091] Furthermore, according to the injection molding method of this embodiment, the molding material M contains 15% by weight or more of the talc, which makes it possible to more reliably reduce the glossiness of the molded product.
[0092] According to the present embodiment, there is provided an injection molding die for filling a molding material M containing a crystalline resin and an additive having a higher elastic modulus and a lower shrinkage rate than the crystalline resin, the cavity C has a surface with a plurality of recesses machined thereon, the recesses have a bottom surface at the opening side where the molding material M flows in, and are shaped like a pyramid or frustum with a cross-sectional area parallel to the bottom surface decreasing as the depth increases, the maximum length of the bottom surface in the flow direction of the molding material is 200 to 400 μm, the depth of the pyramid or frustum in a direction perpendicular to the flow direction is 40 to 150 μm, and the ratio of the maximum length of the bottom surface to the depth is 1.34:1 to 5:1. This allows a molded product having a fine uneven shape to be molded without forming a fine uneven shape on the mold. [Explanation of symbols]
[0093] 1…Injection molding machine 11. Hopper 12…Heating cylinder 13...Screw 14…Nozzle 15…Sprue 16…Runner 17…Gate A, Aa…Arrow AT…Air trap M…Molding material T…Injection mold C...Cavity D...Droplet P…flat plate RB…Rubber SF: Surface of molded product TL…Talc X: Part that does not contact the cavity surface Y: Part in contact with the cavity surface Z...Nesting Za: The part where a recess is formed θ1…Advanced contact angle θ2…Retreating contact angle
Claims
1. 1. An injection molding method comprising filling a molding material containing a crystalline resin and an additive having a higher elastic modulus and a lower shrinkage rate than the crystalline resin into a mold having a cavity with a plurality of recesses on a surface thereof, The recess has a bottom surface at an opening side into which the molding material flows, and has a cone or frustum shape in which the area of a cross section parallel to the bottom surface decreases as the depth increases, The maximum length of the bottom surface in the flow direction of the molding material is 200 to 400 μm; The depth of the cone or the frustum in a direction perpendicular to the flow direction is 40 to 150 μm; The ratio of the maximum length of the base to the depth is from 1.34:1 to 5:
1.
2. The depth is 50 to 150 μm, 2. The injection molding method according to claim 1, wherein a ratio of the maximum length of the bottom surface to the depth is from 2:1 to 4:
1.
3. 3. The injection molding method according to claim 1, wherein the recess has a bottom surface at an opening side through which the molding material flows, and has a pyramid or truncated pyramid shape in which the area of a cross section parallel to the bottom surface decreases as the depth increases.
4. 4. The injection molding method according to claim 3, wherein the recess has a shape of a quadrangular pyramid or a truncated quadrangular pyramid, the bottom surface of which is an opening side through which the molding material flows, and the area of a cross section parallel to the bottom surface decreases as the depth increases.
5. The injection molding method according to any one of claims 1 to 4, wherein a pattern in which recesses of the same shape are repeated a plurality of times is machined on the surface of the cavity.
6. The injection molding method according to any one of claims 1 to 5, wherein the crystalline resin is polypropylene, the additive is talc, and the molding material further contains rubber.
7. The injection molding method according to claim 6 , wherein the molding material contains 15% by weight or more of the talc.
8. An injection molding die for filling with a molding material containing a crystalline resin and an additive having a higher elastic modulus and a lower shrinkage rate than the crystalline resin, There are multiple recesses on the surface of the cavity. The recess has a bottom surface at an opening side into which the molding material flows, and has a cone or frustum shape in which the area of a cross section parallel to the bottom surface decreases as the depth increases, The maximum length of the bottom surface in the flow direction of the molding material is 200 to 400 μm; The depth of the cone or the frustum in a direction perpendicular to the flow direction is 40 to 150 μm; The ratio of the maximum length of the base surface to the depth is from 1.34:1 to 5:1.
Citation Information
Patent Citations
Forming method for article of injection forming type
JP1980159949A
Injection molding of polyolefinic resin
JP1995088902A
Molding method for optical disk substrate and optical disk substrate molded by the molding method
JP2001129853A
Surface material, its manufacturing method and surface material for automotive interior trim
JP2008302549A
Resin molded product
JP2018034428A